Structural studies of a hemicellulose B fraction from the cork of Quercus suber - Asensio, Amparo (Carbohydrate Research, 1987)
Polysaccharide B-2 contains xylose, arabinose, glucose, galactose, 4-0-methylglucuronic acid, and rhamnose in the molar ratio of 17: 12: 12:6:4: 1. The polysaccharide has a backbone of P(1-4)- and P( 1-3)-linked glucopyranosyl, P(lk4)-linked xylopyranosyl, and (1-4)- and (1-6)-linked galactopyranosyl residues. Arabinofuranosyl, rhamnopyranosyl, and some xylopyranosyl and galactopyranosyl groups are present as nonreducing end units. Glucopyranosyluronic acid side chains are attached at 0-2 of some xylose residues. The anomeric configurations of the different glycosyl groups were determined by a study of the chromium trioxide oxidation of the acetylatcd polysaccharide and by nuclear magnetic reasonance spectra of the methylated polysaccharide.
PGPG
Keywords: acid hydrolysis; chromium trioxide oxidation; methylation analysis; NMR; Polysaccharide B-2; Structural analysis